1993
DOI: 10.1002/ijc.2910540321
|View full text |Cite
|
Sign up to set email alerts
|

Superantigen‐induced cytokines suppress growth of human colon‐carcinoma cells

Abstract: We have recently demonstrated that the superantigen staphylococcal enterotoxin A (SEA) conjugated to colon-carcinoma-reactive monoclonal antibodies (MAbs) directs T cells to lyse human colon-carcinoma cells, representing a potential novel tumor therapy. To further analyze the mechanism of antitumor effects of superantigen-activated T cells, we compared the activity of free and MAb-conjugated SEA in a long term in vitro co-culture assay of human peripheral-blood mononuclear cells (PBMC) and colon-carcinoma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 23 publications
2
45
0
Order By: Relevance
“…In this study, we used a well established model of superantigen-induced T cell tolerance (8,12,13,34,35) to investigate downstream defects in TCRmediated regulation of the IL-2-gene in tolerant CD4 ϩ T cells. It has previously been shown that IL-2 protein expression is strongly reduced at all times in tolerant (3ϫ SEA) compared with activated (1ϫ SEA) T cells, both in culture supernatants and in serum samples (8,13) (data not shown).…”
Section: Tolerant Cd4 ϩ T Cells Express Altered Nf B Binding To the Bmentioning
confidence: 99%
“…In this study, we used a well established model of superantigen-induced T cell tolerance (8,12,13,34,35) to investigate downstream defects in TCRmediated regulation of the IL-2-gene in tolerant CD4 ϩ T cells. It has previously been shown that IL-2 protein expression is strongly reduced at all times in tolerant (3ϫ SEA) compared with activated (1ϫ SEA) T cells, both in culture supernatants and in serum samples (8,13) (data not shown).…”
Section: Tolerant Cd4 ϩ T Cells Express Altered Nf B Binding To the Bmentioning
confidence: 99%
“…Cytokines can suppress tumor growth both directly and synergistically. 31 In addition, cytokines can induce LAK activity, activate natural killer cells and macrophages, [32][33][34] facilitate penetration of high molecular weight proteins and upregulate cell adhesion molecules and MHC class II expression on tumor cells. These factors favor additional fusion protein interactions with subsequent SADCC 30,35 and recruit peripheral blood cells into this inflammatory milieu.…”
Section: Discussionmentioning
confidence: 99%
“…4 Superantigen activation of lymphocyte results in cytokines production, proliferation and cytotoxicity and can elicit systemic antitumor immunity. [5][6][7] Superantigen-based antitumor strategies may offer therapeutic promise. 8,9 However, in vivo administration of intact superantigen in sufficient therapeutic amounts risks unwanted cytotoxicity against normal cells because superantigens preferentially direct cytotoxicity against MHC II-positive cells.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, the application leads to transient expansion and subsequent death of T cells with the appropriate V b s. [7][8][9] The characteristics of superantigens can be exploited in diseases where strong immunologic responses are required. This effect has been evaluated in several preclinical [10][11][12][13][14][15][16][17][18][19][20][21][22] and clinical [23][24][25][26] studies of immunotherapeutic approaches in the treatment of cancer where superantigens were used as adjuvant or in fusion molecules with specific antibodies to enhance or maintain the immunologic response. Superantigen administration significantly enhances ineffective antitumor immune responses, resulting in potent and long-lived protective antitumor immunity.…”
mentioning
confidence: 99%